2022
DOI: 10.1111/and.14590
|View full text |Cite
|
Sign up to set email alerts
|

CHD5 gene (rs9434741) might be a genetic risk factor for infertility in non‐obstructive azoospermia and severe oligozoospermia

Abstract: Inability to conceive is one of the health concerns. Chromodomain helicase DNA-binding protein5 (CHD5) gene is a major regulator in the replacement of histone proteins with protamines, the chromatin remodelling in spermatogenesis process. Thus, functional SNPs in this gene can disrupt sperm development. This study aimed to investigate the relationship between CHD5 polymorphism (rs9434741) and male infertility. This case-control study was conducted on 103 infertile and 121 fertile men. CHD5 polymorphism rs94347… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, the surgical removal of the blockage and the testicular puncture are valid in OA, while the current treatment strategies for NOA often fail [ 4 ]. Seeking the underlying biological mechanisms of NOA has attracted increasing attention in the past decades, and some critical genes were uncovered, such as VASA [ 5 ], CHD5 [ 6 ], and MEIOB [ 7 ], providing possible therapeutic targets. Nevertheless, our understandings of the genetic alternation of NOA remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the surgical removal of the blockage and the testicular puncture are valid in OA, while the current treatment strategies for NOA often fail [ 4 ]. Seeking the underlying biological mechanisms of NOA has attracted increasing attention in the past decades, and some critical genes were uncovered, such as VASA [ 5 ], CHD5 [ 6 ], and MEIOB [ 7 ], providing possible therapeutic targets. Nevertheless, our understandings of the genetic alternation of NOA remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…2 Our previous study showed that the distribution of CHD5 genotypes and frequency of alleles were statistically significant between infertile men and control groups and proposed that CHD5 polymorphism (rs9434741) could be associated with the risk of male infertility. 3 We discussed that the CHD5 gene plays a role in sperm density and there was shown a close connection between miR-211 and the CHD5 gene expression. Thus, we decided to study miR-211 expression and compare it between the two groups.We also mentioned that many miRNAs in testicular tissue and semen samples could be investigated.…”
mentioning
confidence: 97%